A potential naphthyl-thiazole-based organic dye and a ditopic chromogenic probe for CN− and Fe3+ with molecular logic functions. (23rd October 2020) - Uahengo, Veikko; Hamukwaya, Eunike N.; Endjala, Paulina T.; Naimhwaka, Johannes H.
Abstract : Dye sensitizers are entities designed primarily to serve the function of harvesting light photons in the functional wavelength, which is centered on charge transfer mechanisms. Abstract : Dye sensitizers are entities designed primarily to serve the function of harvesting light photons in the functional wavelength, which is centered on charge transfer mechanisms. A metal-free dye sensitizer (J ) based on the naphthyl-thiazole groups was synthesized via a one-step reaction mechanism and characterized using UV-vis, 1 H NMR and fluorescence spectroscopic methods. The applications of J were investigated based on its charge transfer mechanisms of photoinduced electron transfer (PET) and excited-state intermolecular proton transfer (ESIPT) mechanisms. Subsequently, J displayed several charge transfer-based properties complementary to dye sensitizers, chemosensing and molecular logic functions. The properties were investigated and studied primarily in acetonitrile (CH3 CN), as a polar solvent of choice. The optical properties of J were investigated through solvatochromism, aided by theoretical recreation, while chemosensing properties were investigated, thereby in the process establishing that J is a ditopic probe which could selectively discriminate CN −, F − and AcO − as well as Fe 3+ in CH3 CN, among other ions. In addition, the reversibility and reproducibility studies substantiated that J exhibits molecular logic operation properties, based on complementary IMP/INH logic functions. Thus, J can be utilized as a colorimetric molecular switch modulated by CN − /Hg 2+ .